2020
DOI: 10.3390/molecules25204736
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Extraction Procedures Based on Natural Deep Eutectic Solvents or Ionic Liquids for Determination of 20-Hydroxyecdysone in Spinach

Abstract: A novel, efficient extraction procedure based on natural deep eutectic solvents (NADES) and ionic liquids (ILs) for determination of 20-hydroxyecdysone (20-E) in spinach has been developed. NADES, the first green extraction agent, with different hydrogen bond donors and acceptors are screened in order to determine extraction efficiencies. NADES consisting of lactic acid and levulinic acid at a molar ratio of 1:1 exhibits the highest yields. ILs, the second green extraction agent, with various cations and anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Taking into consideration the GAC principles, the downscaling of sample treatment has shown some advantages, such as low consumption of samples (10 µL-25 mL), low amounts/volumes of reagents and organic solvents (10-400 µL), a reduction and simplification of procedures, and high enrichment factors. For this reason, although some applications in which larger volumes of DES (even reaching 20 mL) can be found [21,24,29,32,35,37,41,58,69], most hydrophilic DESs have been applied in miniaturized liquid-based extraction techniques (see Table 1). In this sense, DESs have been applied in the three main modes of liquid-phase microextraction (LPME): dispersive liquid-liquid microextraction (DLLME), hollow-fibre liquidphase microextraction (HF-LPME) and single drop microextraction (SDME).…”
Section: Lycium Ruthenicummentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into consideration the GAC principles, the downscaling of sample treatment has shown some advantages, such as low consumption of samples (10 µL-25 mL), low amounts/volumes of reagents and organic solvents (10-400 µL), a reduction and simplification of procedures, and high enrichment factors. For this reason, although some applications in which larger volumes of DES (even reaching 20 mL) can be found [21,24,29,32,35,37,41,58,69], most hydrophilic DESs have been applied in miniaturized liquid-based extraction techniques (see Table 1). In this sense, DESs have been applied in the three main modes of liquid-phase microextraction (LPME): dispersive liquid-liquid microextraction (DLLME), hollow-fibre liquidphase microextraction (HF-LPME) and single drop microextraction (SDME).…”
Section: Lycium Ruthenicummentioning
confidence: 99%
“…On the other hand, its properties, such as viscosity or density, are those that will allow better or worse retention of the analytes [1,6]. In general, hydrophilic DESs tend to have a relatively high viscosity, which makes an effective mass transfer in the extraction processes difficult, so a common practice to reduce their viscosity to suitable values consists in the addition of a known amount of water to hydrophilic DESs using the heating method [15,21,24,25,29,31,33,35,37], in which known concentrations of the three components (HBD, HBA and water) are mixed under constant stirring in a water bath (generally at 50 • C) until a homogeneous and transparent liquid is obtained. In certain cases, water has even been replaced by an organic solvent, such as ethanol (EtOH) or MeOH [43].…”
Section: Lycium Ruthenicummentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, ILs have a wide range of industrial applications. Due to their modulated polarity, acidity, and viscosity, ILs are interesting alternatives for conventional organic solvents [36], hazardous catalysts [37], and absorbent and extraction agents [38,39]. Ionic liquids have also been reported as effective enzyme stabilizers [31,40].…”
Section: Stabilization Of Enzymes Via Ionic Liquidsmentioning
confidence: 99%
“…NADESs (together with ILs) have also been investigated in the extraction of ecdysteroids, and, in particular, 20-hydroxyecdysone, from spinach (Spinacia oleracea L.) and several advantages were found, including higher selectivity, simplicity, efficiency, and rapidity, as well as the recovery and much lower consumption of organic solvents, in comparison with conventional methods [54]. In addition, it has been shown that DESs are also able to extract volatile compounds.…”
Section: Deep Eutectic Solvents (Des)mentioning
confidence: 99%